Millah Ibrahim Dalam Kajian Al-Qur’an:Titik-Temu Agama Ibrahim Menuju Terwujudnya Perdamaian Beragama - Muhammad Tajuddin Romli, Salamah Noorhidayati Dan (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
Millah Ibrahim is the basis that can be used as a reference for interpreting inclusive and exclusive verses. It is hoped that from this millah Ibrahim can be found the sentences of sawa, the meeting point, and the common platform of the Abrahamic religion (Judaism, Christianity, Islam) and foster peace between religions and minimize conflict in the name of religion. This research is library research, by studying and analyzing written sources such as the Qur'an and the Bible as well as scientific books that have a common theme. The approach to be used is the theory of pluralism and esoteric-exoterism. From this study found three meeting points that will lead to peace in religion. 1. Similarities in terms of the origin of religion. Jews, Christians and Muslims meet in one central figure, Ibrahim. 2. Harmony of theology or divinity and continuity of revelation. 3. Sharia togetherness. And the Islam that Muhammad brought was the end of the message carried by the prophets.